Geometrically isomeric Pt(ii)/Fe(ii)-based heterometallo-supramolecular polymers with organometallic ligands for electrochromism and the electrochemical switching of Raman scattering. Issue 40 (26th September 2016) - Chakraborty, Chanchal; Pandey, Rakesh K.; Rana, Utpal; Kanao, Miki; Moriyama, Satoshi; Higuchi, Masayoshi
Abstract : Heterometallo-supramolecular polymers with Pt(ii ) and Fe(ii ) ions introduced alternately were prepared by the 1 : 1 complexation of Fe(ii ) ions with cis - or trans -conformational organo-Pt(ii ) ligands. Abstract : Heterometallo-supramolecular polymers with Pt(ii ) and Fe(ii ) ions introduced alternately ( cis -polyPtFe and trans -polyPtFe ) in a precise way were prepared successfully by the 1 : 1 complexation of Fe(ii ) ions with cis - or trans -conformational organo-Pt(ii ) ligands. The conformational difference between cis - and trans -greatly changed the morphology, crystallinity, ionic conductivity, electrochromic properties, and redox-triggered fluorescence of the polymers. The cis -polyPtFe exhibited better crystallinity and low ionic conductivity, whereas trans -polyPtFe showed an amorphous nature with high ionic conductivity. Both the polymers exhibited reversible electrochromism between purple and yellow colors due to the redox of Fe(ii )/(iii ) upon applying a potential of 0 V or +3 V. The trans -polyPtFe showed better electrochromic stability and response times compared to cis -polyPtFe . In addition, the trans -polyPtFe also showed an improved response in redox-triggered Raman scattering switching compared to cis -polyPtFe over a long time range.